Socialist drive: The First Auto Works and the contradictions of connectivity in the early People's Republic of China. Issue 2 (1st December 2014) - Seow, Victor; Zeller, Thomas
Abstract In 1956, the First Auto Works, the People's Republic of China's first automobile manufacturing plant, began production in the city of Changchun. The vehicles that rolled off its assembly line, most notably the 'Liberation' truck, became part of a growing transportation assemblage through which the socialist economy moved. The automobile drove many of the processes that were to define Chinese Communist rule, including the transformation of the built environment, the pursuit of industrial modernity, the coordination of the planned economy, and the division of city and countryside. Originally intended for the integration of industrial and agricultural sectors, motorised mobility was to become a means of state extraction in rural communes during the tragedy that was the Great Leap Forward.